Ekstraksi Senyawa Bioaktif Kulit Jengkol (Archidendron jiringa) dengan Konsentrasi Pelarut Metanol Berbeda sebagai Pakan Tambahan Ternak Ruminansia: Extraction of Jengkol (Archidendron jiringa) Peel Bioactive Compounds with Different Concentrations of Methanol Solvents as Supplementary Feed for Ruminants - Ridhwan Anshor Alfauzi; Lilis Hartati; Danes Suhendra; Tri Puji Rahayu; Nur Hidayah (Jurnal Ilmu Nutrisi dan Teknologi Pakan (Nutrition and Feed Technology Journal), 2022)
This study aimed to determine the quantitative differences of bioactive compounds in jengkol peel with different concentrations of methanol solvents. Maceration method was used for the extraction process, while the content of bioactive compounds was measured using a uv-vis spectrophotometer. This study was designed in a complete randomized design (CRD) with five treatments of solvents (100% aquadest, methanol 24%, methanol 48%, methanol 72%, and methanol 96%) and four replications. The observed variables in this study included the yield of extracts, tannins, saponins, flavonoids, and total phenols. Data was analyzed using Analysis of Variance (ANOVA). The significant different data was further analyzed using DMRT to compare the treatments’ means. The results showed that the use of methanol solvent at different concentrations had no significant effect on the extract yield (4.50-5.50%) and total phenol (0.97-1.52%), whereas it had a significant effect on the content of tannins, saponins, flavonoids. The lowest tannins (2.98%), saponins (7.64%), and flavonoids (0.18%) content were produced by aquadest 100% solvent. The highest tannins (7,83%) content was produced by methanol 72%, while saponin (20.81%) and flavonoid (0.40%) content were produced by methanol 96%. The use of methanol solvent at a concentration of 72% to 96% is able to attract the most effective bioactive compounds in jengkol peel to utilize as a ruminant feed additive. Key words: Archidendron jiringa, bioactive compound, jengkol peel, methanol